+0  
 
0
95
2
avatar

 

Please help with the above question

 

I will greatly appreciate it.

 Apr 15, 2022
 #1
avatar+124592 
+1

Note that cos AMC =   - cos (AMB)

 

Using the Law of Cosines twice

 

4^2  = (2a)^2 + a^2   - 2 ( 2a)(a)(cos AMC)  ⇒  16 = 5a^2 - 4a^2 ( -cos AMB) ⇒

 

16  = 5a^2 + 4a^2 (cos AMB)  ⇒   cos AMB  =  [16 - 5a^2 ] / [4a^2]        (1)

 

And

 

3^2 =  (2a)^2 + a^2  -  2 (2a)(a) ( cos AMB )   ⇒   9 = 5a^2 -4a^2 ( cos AMB ) ⇒

 

cos AMB  =   [9- 5a^2 ] / (-4a^2)     =   [5a^2 - 9 ] / [4a^2]    (2)

 

Equate (1)  and (2)

 

[16 - 5a^2 ] / [4a^2 ]  =  [5a^2 - 9 ] / [ 4a^2]

 

16 -5a^2  = 5a^2 - 9

 

25  = 10a^2

 

a^2  =  25/10  

 

a =    5  /sqrt 10

 

2a =  10 / sqrt 10  =  BC =   sqrt 10

 

 

cool cool cool

 Apr 15, 2022
edited by CPhill  Apr 15, 2022
 #2
avatar
0

Thanks CPhill

 Apr 15, 2022

24 Online Users